ANALISIS SEDIMENTASI PADA BANGUNAN JETTY MUARA SUNGAI KETAHUN, KABUPATEN BENGKULU UTARA - Arief Fahmi; Muhammad Fauzi; Besperi Besperi (Inersia: Jurnal Teknik Sipil, 2019)
Siltation due to sedimentation is one of the problems that occur in estuar of Ketahun River, Bengkulu Utara. The purpose of this study is to analyze the sedimentation particles and sediment discharge (bed load) at the mouth of Ketahun River. The location of this research is divided into three measurement points located on the downstream (facing the sea), the mouth of the river, and upstream (overlooking the river). The technique used to determine the sedimentation particle is by sieve analisis with various diameters (8,35 mm; 4,76 mm; 2,63 mm; 2,0 mm; 0,84 mm; 0,6 mm; 0,3 mm; 0,149 mm;, 0,074 mm). The percentage is calculated based on the weight of each sample with the results of sedimentation characteristic 0.3 mm smooth sand grains. To determine the basic sediment discharge (bet load) measurement is done directly in the mouth of the Ketahun River to get the river’s morphology and riverbed sediment samples. The samples were then examined in the laboratory, based on sieve analysis test to get the size of a grain diameter (D_35, D_50, D_60, D_90) and sediment specific gravity. The data obtained was then analyzed using empirical formulas-Peter Mayer and Einstein. From the analysis of sediment discharge at the river mouth to year basis obtained results: for method-Peter Mayer with Q_ukur = 2,596 x 10-6 m 3 / s and for the method of Einstein Q_ukur = 4,615 x 10-6 m 3 / sec. Results of the analysis shows that basic sediment discharge increases inline with the increasing river flow.